Frequency of kleptoparasitism by Black Brant Branta bernicla nigricans on Eurasian Coot Fulica atra differs between years and habitats - Shimada, Tetsuo; Kasahara, Satoe; Kurechi, Masayuki; Suzuki, Yasushi; Higuchi, Hiroyoshi (Wildfowl, 2020)
Although socially parasitic feeding interactions are well documented in birds, kleptoparasitism appears uncommon in geese. Kleptoparasitic behaviour of Black Brant Branta bernicla nigricans wintering in northern Japan therefore was studied in 2012/13 and 2013/14. Geese snatched eelgrass Zostera sp. from diving Eurasian Coot Fulica atra which they had procured underwater. During our observations of 1,615 foraging Brants, when three main foraging tactics (pecking, up-ending and kleptoparasitism) were recorded, kleptoparasitism accounted for 31.5% and 11.7% of the total foraging behaviour in these two winters. The annual variation in kleptoparasitism could perhaps reflect differences between years in the availability and accessibility of food in the same habitats.